2020
DOI: 10.1155/2020/7019286
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Microbiological, and Functional Characterization of Kefir Produced from Cow’s Milk and Soy Milk

Abstract: Kefir is a functional beverage that contains lactic and acetic acid bacteria (LAB, AAB) and yeasts. This work’s aim was to study the chemical, microbial, and functional characteristics of kefir produced from cow’s milk and soy milk. After fermentation, free amino acids were 20.92 mg 100 mL−1 and 36.20 mg 100 mL−1 for cow’s milk and soy milk kefir, respectively. Glutamic acid was majority in both, suggesting that microbial proteolysis leads to an increase in free amino acids including glutamic acid. 108–109 CFU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
29
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 36 publications
5
29
0
5
Order By: Relevance
“…However, there was no antimicrobial effect against Pseudomonas aeruginosa [ 17 , 60 ]. Other organic acids present in kefir, such as acetic and pyruvic acid, also demonstrated an antimicrobial effect when administered together with lactic acid [ 14 , 31 , 70 ]. Kakisu et al [ 31 ] identified that organic acids act against the germination of B. cereus spores in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there was no antimicrobial effect against Pseudomonas aeruginosa [ 17 , 60 ]. Other organic acids present in kefir, such as acetic and pyruvic acid, also demonstrated an antimicrobial effect when administered together with lactic acid [ 14 , 31 , 70 ]. Kakisu et al [ 31 ] identified that organic acids act against the germination of B. cereus spores in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Smaller fractions present in kefir, such as bioactive peptides, also demonstrated an antioxidant effect. An enhancement in scavenging ability of oxidized 2,2′-zino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) ranged from 2% to 25.6% for sheep's milk kefir and 35.8% for cow's milk kefir both compared to control [ 14 , 64 ]. A significant improvement (111.6%) in oxygen radical absorbance capacity (ORAC) for cow's milk kefir confirmed the antioxidant activity of bioactive peptides [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their colonisation in the intestinal tract improves the intestinal microbiota balance, strengthens the defence against pathogens, and improves oxidative stress resistance. In addition, other beneficial effects are lowering of blood cholesterol levels, synthesis of some vitamins, anticarcinogenic and antimicrobial metabolites (Gamba et al 2020).…”
mentioning
confidence: 99%
“…citrovorum, and Str. diacetylactis), and its LAB content varies depending on the origin of kefir grains (Gamba et al 2020).…”
mentioning
confidence: 99%